Early identification of alcohol use in workers and applying brief interventions - Ayub, Sandra Regina Chalela; Martins, Raul Aragão (Revista de Administração da UFSM, 2021)
Purpose: This study aimed to identify the pattern of alcohol consumption in workers and then apply a brief intervention (BI) in those who presented a pattern of excessive drinking in order to achieve withdrawal or at least decrease consumption. Design/methodology/approach: This was an exploratory, descriptive, and quasi-experimental study carried out in four stages: initial screening, interview, BI, and follow-up sessions. Two hundred and thirty workers participated in the first stage, and sociodemographic and alcohol use disorders identification (AUDIT) data were collected, and thirty-four percent of workers were classified as positive (at risk, under harmful use, or alcohol dependent). Afterward, the drinking pattern was investigated by applying the modified brief drinker profile and alcohol dependence scale (ADS). The positive participants in the AUDIT and ADS were divided into the experimental and control groups. In the third stage, the BI was performed in the experimental group. In the follow-up sessions (the fourth stage), the AUDIT was applied three months and six months after the BI to the experimental and control groups for comparison purposes. Findings: The results showed that the BI was effective. In all follow-up sessions, the data revealed that the experimental group had lower amounts of drinking. The control group also reduced drinking, albeit not in the same proportion as the experimental group. We believe that these results can contribute to implementing programs aimed at employee health. Originality: Applying the BI on workers with excessive drinking patterns.